1039 ZAMIA DECUMBENS: Cycadales, Zamiaceae. (26th August 2022) - Herrera‐Blitman, Natalia; Calonje, Michael; Meerman, Jan; Aguilar, Rudy; Meerow, Alan W.; Francisco‐Ortega, Javier; Griffith, M. Patrick
Summary: Zamia decumbens Calonje, Meerman, M.P.Griff. & Hoese, a threatened cycad species from Belize, is showcased and illustrated based on field observations as well as plants cultivated in the ex situ conservation living collections of Montgomery Botanical Center (MBC) in Coral Gables, Florida. This once obscure species was described in 2009, studied in the field, and introduced into ex situ conservation collections at MBC and other botanical gardens around the world. At MBC, the living collection of Z. decumbens plants has been used to conduct additional research to advance further our knowledge about cycads and to develop guidelines for building living plant collections in support of conservation. In this contribution we discuss this species and its cultivation at the ex situ conservation collection at MBC, using it to illustrate the important role botanical gardens can play in protecting threatened species and advancing our knowledge about them.